2010
DOI: 10.1287/mnsc.1100.1209
|View full text |Cite
|
Sign up to set email alerts
|

Do Inventory and Gross Margin Data Improve Sales Forecasts for U.S. Public Retailers?

Abstract: Firm-level sales forecasts for retailers can be improved if we incorporate cost of goods sold, inventory, and gross margin (defined by us as the ratio of sales to cost of goods sold) as three endogenous variables. We construct a simultaneous equations model, estimated using public financial and nonfinancial data, to provide joint forecasts of annual cost of goods sold, inventory, and gross margin for retailers using historical data. We show that sales forecasts from this model are more accurate than consensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 19 publications
2
116
0
Order By: Relevance
“…This occurs when there are multiple dependent variables each influencing at least one other dependent variable. An example of the simultaneity problem in empirical OM research is found in Kesavan et al (2010), in which the authors argue that the cost of goods sold, gross margin, and inventory levels are simultaneously determined.…”
Section: Simultaneity Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs when there are multiple dependent variables each influencing at least one other dependent variable. An example of the simultaneity problem in empirical OM research is found in Kesavan et al (2010), in which the authors argue that the cost of goods sold, gross margin, and inventory levels are simultaneously determined.…”
Section: Simultaneity Biasmentioning
confidence: 99%
“…11 Gaur et al (2005) show that inventory is simultaneously determined with other firm operational outcomes, which suggests that simultaneous equations models would be appropriate empirical tools. Kesavan et al (2010) apply simultaneity bias correction in their estimation model to study the relationship among cost of goods sold, gross margin, and inventory levels.…”
Section: Research Implications For Om and Conclusionmentioning
confidence: 99%
“…During the last twenty years, there has been considerable research on the performance of sell-side analysts who work for brokerage firms, investment banks and independent research firms (Elgers, Lo, and Murray, 1995, Hilary and Menzly, 2006, Kesavan, Gaur, and Raman, 2010. 1 But because of data limitations, there has been very little research on buy-side analysts-that is analysts working for institutional investors such as mutual funds, pension funds, and hedge funds.…”
Section: Introductionmentioning
confidence: 99%
“…With a fixed numerator, a larger production reduces average fixed cost per unit. A lower average fixed cost may, in turn, increase the gross margin thereby increasing the attractiveness of higher inventory maintenance (Rumyantsev and Netessine 2007, Li, Min et al 2008, Kesavan, Gaur et al 2010, Kesavan and Mani 2013, Li, Lundholm et al 2013). …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This perverse incentive may stem from the pressure of the managers to reduce the unit cost of production and improve gross margin especially in the context of cash-constrained firms in highly competitive situations (Kothari 2001, Wang 2002, Kesavan, Gaur et al 2010, Li, Lundholm et al 2013). …”
Section: Theoretical Backgroundmentioning
confidence: 99%